Land Cover and Climate Change May Limit Invasiveness of Rhododendron ponticum in Wales - Manzoor, Syed A.; Griffiths, Geoffrey; Iizuka, Kotaro; Lukac, Martin (Frontiers in Plant Science, 2018)
Invasive plant species represent a serious threat to biodiversity inducing, with sustained global effort to eradicate or at least control the spread of this phenomenon. Current distribution ranges of many invasive species are likely to be modified in the future by land cover and climate change.; Thus invasion management can thus be made more effective by forecasting the potential trend of invasion. Rhododendron ponticum (L.) is an aggressive invasive species which appears well suited to western areas of the UK. We made use of MAXENT modelling environment to develop a current distribution model and to assess the likely effects of land cover and climatic conditions (LCCs) on future distribution of this species in the Snowdonia National park in Wales. Six global circulation models (GCM’s) (global circulation models) and two representative concentration pathways (RCP’s) (representative concentration pathways), together with a land cover simulation for 2050 were used to investigate species’ response to future environmental conditions. Having considered a range of environmental variables as predictors and carried out AICc-based model selection, we find that under all LCCs considered in this study, the range of R. ponticum in Wales is likely to contract in the future. Land cover and topographic variables were found to be the most important predictors forof the distribution of R. ponticum. This information, together with maps indicating future distribution trends will aid the development of mitigation practices to control R. ponticum.